Artist-dealer agreements and the nineteenth-century art market the case of Gustave Coûteaux - Baetens, Jan Dirk 1977- (2020)
The market for contemporary art in the second half of the nineteenth century was deeply affected by the introduction and widespread use of long-term contracts between artists and their dealers. This article examines the legal and commercial logic behind these agreements and their impact on the production, distribution, and consumption of art. It draws mainly from the uniquely preserved contracts and correspondence of the Belgian art dealer Gustave Coûteaux. The article also provides complete transcriptions of the seven successive contracts concluded between Coûteaux and his most successful artist, Henri Leys, from 1841 to 1865.
Keywords: Coûteaux, Gustave -- 1815-1873; Leys, Henri -- 1815-1869; Geschichte 1850-1880; Künstler; Kunsthändler; Kunstmarkt; Vertrag; Kunsthandel; Belgien